(untitled) (Baghdad Science Journal, 2025)
the current study Included, evaluation the impact of Nitrofurantoin drug on liver in albino mice, 128 male albino mice have been used . Animals treared with (150,200 Mg/Kg) for 8 weeks . NFI caused histological changes in liver represented by , swelling of hepatocytes, disappearance of radial arrangement , vaculation of liver cells , increasing of kupffer cells and appearance of giant cells. NFT caused Congestion of blood vessels and infiltration of inflammatory cells in liver in all used concentrations.